2015
DOI: 10.1002/ange.201501100
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Amide‐Derived Non‐Biaryl Atropisomers as Highly Efficient Ligands in Silver‐Catalyzed Asymmetric Cycloaddition Reactions

Abstract: The synthesis of a series of aromatic amide-derived non-biaryl atropisomers with a phosphine group and multiple stereogenic centers is reported. The novel phosphine ligands exhibit high diastereo-and enantioselectivities (up to > 99:1 d.r., 95-99 % ee) as well as yields in the silver-catalyzed asymmetric [3+2] cycloaddition of aldiminoesters with nitroalkenes, which provides a highly enantioselective strategy for the synthesis of optically pure nitro-substituted pyrrolidines. In addition, the experimental resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 94 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…The structural and stereochemical assignments of the pyrrolidine derivatives were made by comparing with those found in the literature. Based on the observed stereochemistry of the products and the literature findings by Bai et al, 22,23 we propose the transition state shown in Figure 2. In this transition state, the CFAM4 ligand, imine, and the dipolarophile are coordinated to the silver ion in such a way that the cycloaddition takes place from the si-side of the imine nitrogen in an endo-mode.…”
Section: Resultssupporting
confidence: 63%
“…The structural and stereochemical assignments of the pyrrolidine derivatives were made by comparing with those found in the literature. Based on the observed stereochemistry of the products and the literature findings by Bai et al, 22,23 we propose the transition state shown in Figure 2. In this transition state, the CFAM4 ligand, imine, and the dipolarophile are coordinated to the silver ion in such a way that the cycloaddition takes place from the si-side of the imine nitrogen in an endo-mode.…”
Section: Resultssupporting
confidence: 63%
“…Inspired by their previous work on asymmetric [3 + 2] cycloadditions based on a Michael-addition-initiated cyclization reaction, 203 Xu et al 204 reported the Michael addition of glycine aldimino esters to chalcones using the Ag(I)/Xing-Phos (L63−AgOAc) catalyst, providing excellent outcomes (up to >20:1 dr and 97% ee; Scheme 42). The cyclization products were obtained with cis-isomers when the 1,4-addition products were further treated with HCl, which could be easily transformed to the trans-isomers under alkaline conditions.…”
Section: Conjugate Addition Of Aldehydes and Ketonesmentioning
confidence: 99%
“…[19] These unique non-biaryl atropisomers not only exist in bioactive molecules, but also can be used as chiral auxiliaries, ligands and catalysts. [20,21] However, compared to the well-established axially chiral biaryls, the asymmetric catalytic processes for the formation of atropisomeric amides are still underdeveloped (Scheme 1a). This may be attributed to the less stable axis and hence less rigid skeleton.…”
mentioning
confidence: 99%